2012
DOI: 10.1113/jphysiol.2012.229468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemostimuli on [Ca2+]i responses of rat aortic body type I cells and endogenous local neurons: comparison with carotid body cells

Abstract: Key points• Mammalian aortic bodies (ABs) are putative peripheral chemoreceptor cells presumed to monitor the oxygen content of arterial blood, although their direct chemosensitivity has never been previously demonstrated at the cellular level.• We used Ca 2+ imaging to show for the first time that a variety of stimuli, including hypoxia, isohydric and acidic hypercapnia, and isocapnic acidosis, caused increases in cytosolic [Ca 2+ ] in AB chemoreceptor cells.• We also showed that some local neurons, known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 45 publications
4
50
0
Order By: Relevance
“…1–, Panx‐1 was not expressed in tyrosine hydroxylase (TH)‐positive chemoreceptor glomus or type I cells but, consistent with positive type II cell staining, it was strongly expressed in contiguous cells with processes that appeared to ensheath type I cells ( n = 3). In dissociated CB cultures, type II cells may occur interspersed within glomus cell clusters (GCs), and often as solitary isolated cells near the periphery of the GCs (Nurse & Fearon, 2002; Piskuric & Nurse, 2012). Within GCs in culture, Panx‐1 labelled cells with the expected characteristics of type II cells; this labelling pattern was separate and distinct from TH‐positive type I cells as exemplified in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1–, Panx‐1 was not expressed in tyrosine hydroxylase (TH)‐positive chemoreceptor glomus or type I cells but, consistent with positive type II cell staining, it was strongly expressed in contiguous cells with processes that appeared to ensheath type I cells ( n = 3). In dissociated CB cultures, type II cells may occur interspersed within glomus cell clusters (GCs), and often as solitary isolated cells near the periphery of the GCs (Nurse & Fearon, 2002; Piskuric & Nurse, 2012). Within GCs in culture, Panx‐1 labelled cells with the expected characteristics of type II cells; this labelling pattern was separate and distinct from TH‐positive type I cells as exemplified in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because rat type II cells express P2Y2 receptors whose activation leads to a rise in cytosolic Ca 2+ (Xu et al . 2003; Piskuric & Nurse, 2012), we tested whether ATP could induce Panx‐1 channel opening and consequently, membrane depolarization. During perforated‐patch whole‐cell recording, random sampling within GCs occasionally revealed cells with type II characteristics as observed in earlier studies (Duchen et al .…”
Section: Resultsmentioning
confidence: 99%
“…For example, whereas ϳ31% of Nox cells responded to hypoxia with a detectable (Ͼ20 nM) rise in [Ca 2ϩ ] i , as many as ϳ87% and ϳ74% did so after exposure to CHox and treatment with DFX, respectively. Furthermore, whereas ϳ26% of Nox cells were sensitive to acid hypercapnia, ϳ69% of CHox cells and ϳ50% of DFX cells were sensitive to acid hypercapnia; however, these [Ca 2ϩ ] i measurements are likely to be underestimated because of the pH sensitivity of the dye fura 2 (43). Thus…”
Section: By 2-tailed T-test)mentioning
confidence: 92%
“…[Ca 2ϩ ]i was measured as described in previous studies from this laboratory (43). Briefly, cultured cells were loaded with the fluorescent Ca 2ϩ indicator fura 2-AM (2.5 M) in BBS for 30 min at 37°C in an incubator with an atmosphere of 95% air-5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo studies using Trpa1-deficient mice showed that hyperoxia-and mild hypoxia (15% O 2 )-induced enhancement of vagal afferent nerve activities is severely impaired by Trpa1 gene knockout. In addition, a variety of stimuli, including hypoxia, have been shown to increase intracellular Ca 2+ concentration in AB chemoreceptor cells (Piskuric & Nurse 2012). Furthermore, some local neurones, including vagal and sensory neurones that are known to be associated with AB paraganglia in situ, generated robust Ca 2+ responses to hypoxia, suggesting that these neurones serve a sensory function in local cardiorespiratory reflexes.…”
mentioning
confidence: 99%